Transformasi Pendidikan STEM Dalam Menstimulasi Keterampilan Berpikir Kritis dan Kreatif Siswa: Sebuah Tinjauan Naratif - Gunawan, Gunawan; Herayanti, Lovy (Indonesian Publication Center, 2021)
The Industry 4.0 era demands graduates possessing 4C competencies, specifically critical and creative thinking skills. Science, Technology, Engineering, and Mathematics (STEM) education is considered the most relevant approach to addressing these challenges. This study aims to provide a narrative review of the transformation of STEM education in stimulating students' higher-order thinking skills, based on literature published between 2015 and 2020. Through an analysis of selected journal articles, this study identifies a paradigm shift in learning from conventional methods toward the integration of technology and inquiry pedagogy. The key findings indicate that the use of immersive technologies, such as virtual laboratories and interactive multimedia, has proven effective in visualizing abstract concepts (particularly in Physics), thereby directly enhancing student creativity. Furthermore, the integration of learning models such as Problem-Based Learning (PBL) and Challenge-Based Learning (CBL) within the STEM framework provides the necessary scaffolding to train critical thinking dispositions. This article concludes that the transformation of STEM education relies not merely on technology adoption, but on the synergy between digital tools and problem-centered instructional design.